MaHPCA1 alleviates chilling injury in banana fruit - Yu Hou; Peipei Fan; Xiangbin Xu; Zhengke Zhang; Yonggui Pan; Lanhuan Meng; Lisha Zhu; Haiming Chen; Jianbo Xiao; Yueming Jiang; Jiali Yang (Postharvest Biology and Technology, 2026)

FreqChange: Frequency-aware spatiotemporal learning with prior guidance for semantic change detection in remote sensing images - Haiyan Huang; Zhenfeng Shao; Duowang Zhu; Xiao Huang; Ruiqian Zhang; Qimin Cheng; Jindou Zhang; Yueming Duan; Deren Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Nitrogen nutrition diagnosis of sweetpotato based on critical nitrogen dilution curve under different water conditions - Xu Zhao; Ximing Xu; Jing Yu; Minghuan Jin; Siyu Wang; Yueming Zhu; Guoquan Lu; Zunfu Lv (Irrigation Science, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

Arbuscular mycorrhizal symbiosis enhances microbial contribution to mineral-associated organic carbon persistence in soil: Insights from soil microbial community and microbial necromass carbon - Yin LIU; Jin QIAN; Yueming ZHU; Jing HU; Bianhe LU; Yuxuan HE; Junwei SHEN (Pedosphere, 2026)

Does algal trophic mode affect the removal of norfloxacin? Insights from Tetradesmus obliquus - Musheng Ji; Jin Qian; Xiaxia Li; Yueming Zhu; Yin Liu; Bianhe Lu; Sijing Tang; Junwei Shen; Yuhang Zong (Journal of Hazardous Materials, 2026)

The combined exposure to antibiotics intensified the phytotoxicity of perovskite composite nanoparticles to Phragmites communis - Yuxuan He; Yueming Zhu; Jin Qian; Bianhe Lu; Sijing Tang; Yin Liu; Junwei Shen; Musheng Ji (Journal of Environmental Management, 2026)

Insight into the pollution potential of different ecological types of lakes from the perspective of dissolved organic matter characteristics: Field and experimental evidence - Yang Deng; Longmian Wang; Yueming Zhu; Xiang Zhu; Qingqing Pang; Yuying Ma; Fuquan Peng; Lei Xie; Xiaoguang Xu; Qiu Jin; Guoxiang Wang; Fei Yang; et al. (Journal of Hydrology, 2025)

Numerical modeling of multi-directional lateral behaviour of pile foundations for offshore wind turbines in clay - Shasha Ren; Deqiong Kong; Yueming Du; Yuan Chen; Bin Zhu (Ocean Engineering, 2025)

Pore structure modulation and surface functionalization boosted adsorption of PFAS on porous carbon: Experimental and theoretical investigations - Bei Zhang; Daiki Moriyama; Thilini Maheshika Herath; Huan Zhao; Yuqiao Bai; Yueming Dang; Wei Liu; Hiromichi Kato; Koichi Yamamoto; Yasuhide Mochizuki; Naoki Arimitsu; Akira Nakajima; et al. (Journal of Hazardous Materials, 2025)

The role of amino acids in delaying the pulp breakdown of litchi fruit during postharvest storage - Lei Wei; Ziming You; Ping Liu; Hong Zhu; Xuewu Duan; Yueming Jiang; Ze Yun (Food Chemistry, 2025)

The role of nano hydrogen water on fruit quality and antioxidant system of dragon fruit during postharvest storage - Ziming You; Lei Wei; Shujing He; Hong Zhu; Xuewu Duan; Yueming Jiang; Ze Yun (Food Chemistry, 2025)

MOFs-derived FeNi bimetallic phosphide with tightly coupled heterogeneous interface for PMS activation - Xiaoyang Liu; Yueming Zhu; Minghui He; Chenyu Zhang; Gancheng Zuo; Yuting Wang; Shaogui Yang; Huan He (Chemical Engineering Journal, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Gene flow network of four major pigments and role of LcmiR2111-KFB14 in pericarp browning of litchi during storage - Jiaqi Xiao; Shuting Zhang; Yijie Zhou; Xiangjin Kong; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2025)

The impact of land use on the composition of dissolved organic matter and its relationship with microbes in a river basin in Northwestern China: Insights into microbial community structure and metabolic function - Xiang Zhu; Xinhua Gao; Yueming Zhu; Jingjie Huang; Fuquan Peng; Qingqing Pang; Fei Yang; Lei Xie; Zulin Hua; Longmian Wang (Journal of Environmental Management, 2025)

Polystyrene nanoplastics reshape the peatland plants (Sphagnum) bacteriome under simulated wet-deposition pathway: Insights into unequal impact of ecological niches - Sijing Tang; Jin Qian; Yueming Zhu; Bianhe Lu; Yuxuan He; Yin Liu; Kailin Xu; Junwei Shen (Journal of Hazardous Materials, 2025)

Tyr-Asp treatment delays senescence in litchi fruit by enhancing redox balance and maintaining energy homeostasis - Ruan Zhiyan; Yanxuan Zhu; Mengting Liu; Yijie Zhou; Xinguo Su; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Corrigendum to ''Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis'' [Postharvest Biol. Technol., vol., 222, April 2025, 113338] - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Evaluation of factors influencing full wave equation depth migration - Anyu Li; Yueming Ye; Xiangyu Zhu; Tao Liu; Huimin Zhang; Yong Xia (Journal of Applied Geophysics, 2025)

New insights of flavonoid glycosidases and their application in food industry - Yingjun Liu; Qiuxia Yang; Yushan Guo; Yueming Jiang; Hong Zhu; Bao Yang (Critical Reviews in Food Science and Nutrition, 2025)

Novel encoding technique to evolve convolutional neural network as a multi-criteria problem for plant image segmentation - Alwaseela Abdalla; Yueming Zhu; Fangfang Qu; Haiyan Cen (Computers and Electronics in Agriculture, 2025)

Arabinogalacturonan in functional food “Astragalus membranaceus root”: Structure and immunomodulatory activity - Zhili Sheng; Hui Liu; Bailin Li; Hong Zhu; Yueming Jiang; Bao Yang (Food Hydrocolloids, 2025)

Phytosulfokine treatment delays browning of litchi pericarps during storage at room temperature - Hanzhi Liang; Yanxuan Zhu; Zhiwei Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Sustainable utilization of cultivated land resources based on "element coupling-function synergy" analytical framework: A case study of Guangdong, China - Hao Yang; Runyan Zou; Yueming Hu; Lu Wang; Yingkai Xie; Zhengxi Tan; Zhiqiang Zhu; A.-Xing Zhu; Jianzhou Gong; Xiaoyun Mao (Land Use Policy, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Co-removal and recycling of Ba2+ and Ca2+ in hypersaline wastewater based on the microbially induced carbonate precipitation technique: Overlooked Ba2+ in extracellular and intracellular vaterite - Huaxiao Yan; Xiaofei Zhu; Zhiyong Liu; Shengping Jin; Jilai Liu; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; et al. (Journal of Hazardous Materials, 2024)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

A new curve of critical leaf nitrogen concentration based on the maximum root dry matter for diagnosing nitrogen nutritional status of sweetpotato - Zhi Zhang; Ximing Xu; Minghuan Jin; Jiacheng Bai; Xing Shu; Lijuan Deng; Siyu Wang; Yueming Zhu; Yuheng Liu; Guoquan Lu; Zunfu Lv (European Journal of Agronomy, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

Involvement of LcmiR482e-LcACA2 mediated energy metabolism in senescence of harvested litchi fruit - Jiaqi Xiao; Yunyun Xie; Xiangjin Kong; Kuan Peng; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2024)

Changes in dilution curves of critical nitrogen concentration in sweetpotato under different potassium conditions - Lijuan Deng; Ximing Xu; Yueming Zhu; Weichen He; Minghuan Jin; Yuheng Liu; Guoquan Lu; Zunfu Lv (Field Crops Research, 2023)

Naturally occurring prenylated stilbenoids: food sources, biosynthesis, applications and health benefits - Shengtao Bo; Sui Kiat Chang; Hong Zhu; Yueming Jiang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2023)

Revealing the crystal phase effect of CeO2 in spinel-based nanocatalysts toward the peroxymonosulfate activation for organics degradation - Yuxuan He; Yueming Zhu; Jin Qian; Peifang Wang; Yuhang Zhang; Kailin Xu; Bianhe Lu; Yin Liu; Junwei Shen (Chemical Engineering Journal, 2023)

Source Apportionment of Soil Heavy Metal(Loid)s in Farmland Using Diverse Models: A Comparative Assessment in the Yellow River Delta - Wei Huang; Shuhuan Wang; Lu Wang; Yingqiang Song; Yue Zhu; Hao Yang; Yingkai Xie; Yueming Hu (Journal of Marine Science and Engineering, 2023)
The rapid development of industrialization and urbanization has posed serious challenges for coastal farmland ecosystems. Source apportionment of soil heavy metals is an effective way for the detection of non-point source pollution in farmland to help support the high-quality development of coastal agriculture. To this end, 113 surface soil samples were collected in the coastal delta of China, and the contents of As, Cd, Cr, Cu, Ni, Pb, and Zn were determined. A variety of models were integrated to apportion the source of soil heavy metals, including positive matrix factorization (PMF), geographical detector (GD), eXtreme gradient boosting (XGBoost), and structural equation modeling (SEM). The result of PMF models revealed that there was collinearity between various heavy metals, and the same heavy metal may have a mixed source. The XGBoost model analysis indicated that there were significant non-linear relationships between soil heavy metals and source factors. A synergy between air quality and human activity factors was the key source of heavy metal that entered the study area, based on the results of the GD. Furthermore, the input path effect of heavy metals in the soil of the study area was quantified by SEM. The balance of evidence from the above models showed that air quality (SO2 and NO2) and factories in the study area had the greatest impacts on Cd, Cr, and Zn. Natural sources were dominant for Pb, while As, Cu, and Ni were contributed by soil parent material and factories. The above results led to the conclusion that there was a cycle path in the study area that continuously promoted the migration and accumulation of heavy metals in farmland soil; that is, the heavy metals discharged during oil exploitation and smelting entered the atmosphere and then accumulated in the farmland soil through precipitation, atmospheric deposition, and other paths. In this study, it is shown that a variety of models can be used to more comprehensively assess the sources of soil heavy metals. This approach can provide effective support for the rapid prevention and decision-making management of soil heavy metal pollution in coastal areas.

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Multiple metabolomics comparatively investigated the pulp breakdown of four dragon fruit cultivars during postharvest storage - Qixian Wu; Huijun Gao; Ziming You; Zhengke Zhang; Hong Zhu; Mingyang He; Junxian He; Xuewu Duan; Yueming Jiang; Ze Yun (Food Research International, 2023)

Degradation of water-soluble polysaccharides in pulp of litchi during storage - Zhongsuzhi Chen; Meiying He; Yijie Zhou; Xi Chen; Hong Zhu; Bao Yang; Yueming Jiang; Hongxia Qu (Food Chemistry, 2023)

The Impact of Multiple Pond Conditions on the Performance of Dike-Pond Extraction - Jinhao Zhou; Wu Zhou; Qiqi Zhou; Yuanhui Zhu; Fei Xie; Shen Liang; Yueming Hu (Fishes, 2022)
Dike-ponds in fisheries often present multiple pond conditions such as pure, suspended sediment, water bloom, semidry conditions, etc. However, the impact of these conditions on the performance of extracting dike-pond from remote sensing images has not been studied. To solve this problem, we explore the existence of such impacts by comparing the performance of four rule-based methods in two groups of test regions. The first group has few multiple pond conditions, while the second has more. The results show that various measure values deteriorate as the proportion of multiple pond conditions in the regions increases. All four methods performed worse in the second group than the first, where the overall accuracy decreased by 8.80%, misclassification error increased by 3.69%, omission error raised by 10.53%, and correct quantity rate dropped by 8.23%, respectively. The extraction method that ingested multiple pond conditions performed indistinguishably from the other methods in the first group. However, it outperformed the other methods in the second group, with a 4.22% improvement in overall accuracy, a 10.25% decrease in misclassification error, and a 19.03% increase in the correct quantity rate. These findings suggest that multiple pond conditions can negatively impact the extraction performance and should be considered in dike-pond applications that require a precise pond size, number, and shape.

Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Shengpeng Li; Ruyue Wang; Yueming Jiang; Yanyu Li; Lin Zhu; Jianfeng Feng (Frontiers in Marine Science, 2022)
The last 30 years have witnessed the degradation and loss of function in the ecosystem of the Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of the Bohai Sea in recent years. In this study, we examined the seasonal variation of food webs in artificial reefs of Juehua Island by the Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency, and ecosystem maturity have increased from summer to autumn. However, the food web stability of artificial reefs has no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton, and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. This study suggests that stability is a more robust indicator for ecosystem assessment and could provide useful information in future restoration plans of the marine ecosystem.

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Protective Effects of Sodium Para-aminosalicylic Acid on Manganese-Induced Damage in Rat Pancreas - Xiaojuan Zhu; Bingyan Xie; Dianyin Liang; Wenxia Qin; Lin Zhao; Yue Deng; Pingjing Wen; Fang Xu; Michael Aschner; Yueming Jiang; Shiyan Ou (Biological Trace Element Research, 2021)

Crop resistant starch and genetic improvement: a review of recent advances - Jian Xia; Dong Zhu; Ruomei Wang; Yue Cui; Yueming Yan (Theoretical and Applied Genetics, 2018)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

Molecular cloning and potential function prediction of homologous SOC1 genes in tree peony - Shunli Wang; Margherita Beruto; Jingqi Xue; Fuyong Zhu; Chuanjiao Liu; Yueming Yan; Xiuxin Zhang (Plant Cell Reports, 2015)

Zircon ages and geochemical data of the Biluutiin ovoo ophiolite: implication for the tectonic evolution of South Mongolia - Mingshuai Zhu; Laicheng Miao; Munkhtsengel Baatar; Fochin Zhang; Chimedtseren Anaad; Shunhu Yang; Yueming Li (International Geology Review, 2014)

Overexpression of d-psicose 3-epimerase from Ruminococcus sp. in Escherichia coli and its potential application in d-psicose production - Yueming Zhu; Yan Men; Wei Bai; Xiaobo Li; Lili Zhang; Yuanxia Sun; Yanhe Ma (Biotechnology Letters, 2012)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

Overexpression and characterization of a thermostable trehalose synthase from Meiothermus ruber - Yueming Zhu; Dongsheng Wei; Jun Zhang; Yufan Wang; Hengyi Xu; Laijun Xing; Mingchun Li (Extremophiles, 2010)

Preserved amplitude migration based on the one way wave equation in the angle domain - Yueming Ye; Zhenchun Li; Xufeng Zhu; Zhaoqi Tong (Applied Geophysics, 2009)

Berechnung von Temperatur- und Spannungszuständen in RCC-Staumauern - Yueming Zhu; Stephan Semprich; Yuefeng Ma; Weimin Cao; Hong Wang (WASSERWIRTSCHAFT, 2007)

Durchlässigkeitseigenschaften und Drainagemaßnahmen von RCC-Staumauern - Yueming Zhu; Stephan Semprich; Erich Bauer; Jing Li (WASSERWIRTSCHAFT, 2005)